STRATEGI KOMUNIKASI TERHADAP ANAK USIA DINI - Husnul Bahri (Universitas Islam Negeri Fatmawati Sukarno, 2018)
Communication as a process in delivering messages to achieve a goal, the main component is a communica- tor or source message, communicant or recipient of the message and the message itself. In the learning process for early childhood, communication should be developed with strategies tailored to the growth and development of children, one the foccus of study is the development to the language of children who will give a big influence on communication strategies against early age. The popular mistake communicators is an adults in the language of communication, and communication barriers for children should be great interest in devising communication strategies. three things that are very urgent is the use of appropriate terms, continuoust, and the presence of cues to switch themes